Tecnologia educativa no ensino de enfermagem em contracepção - Aquino, Priscila de Souza (2010)
The use of technology has increased considerably in society and one of the areas that has been adapting to such use is health. Increasingly, communication technologies are gaining ground in daily life and in health education is no different. Distance education has emerged as a possibility of dissemination of information with greater convenience, autonomy and participation of the subjects. Thus, realizing the importance of developing appropriate educational tools for learning environments, this study was carried out with the following objectives: to determine the effects of educational technology’s use in learning of nursing students about contraception; to implement a educational technology’s on contraception for nursing students; to assess the learning of nursing students about contraception after use of the virtual environment; to compare the knowledge of students who used the virtual environment to those using traditional method of learning. This is an almost-experimental, comparative and of intervention study, conducted on 62 nursing students in the seventh semester and enrolled in the Nursing in Care’s Process in Sexual and Reproductive Health discipline, at UFC, between september 2009 and april 2010. The intervention group used the AVA and answered a questionnaire pre and post-test about contraception. The same instrument was administered to students in the control group, participants in the traditional class with the same information that was in the AVA. All ethical aspects were respected. The data showed a predominantly female population, single, childless, with easy access to computers and internet, reporting knowledge of the methods, but not substantially. Furthermore, many methods users were mainly male condom and oral contraceptive, indicating greater knowledge of these two methods. Some questions showed a significant increase in post-test in the intervention group, especially those related to the hormonal, surgical methods, natural and behavioral methods, and barrier methods. However, significant reductions were observed at post-test articles related to sexual and reproductive rights and the Intrauterine device (IUD). Prevailed in the study that the differences between the success in the post-test of the two groups showed no statistically significant differences. It was 47 questions submitted, 33 increased at post-test, wich 18 statistically significant, 9 had reductions in the post-test, with 6 statistically significants and 5 remained with the same amount of the pre-test. Of the 9 issues that presented significant differences when comparing the post-test of two groups, 5 showed higher accuracy in the intervention group. It is concluded that the AVA provides pertinent information to contraception’s area, being suitable for use in the classroom, not as a replacement, but with the possibility of complementing traditional teaching. No differences in post-test groups indicates that educational technology has achieved the results obtained in the face modality. Furthermore, new studies become necessary in order to evaluate the effects of such technology on student performance.